ATRT-15. SPINAL CORD ATYPICAL TERATOID/RHABDOID TUMORS (AT/RT) IN CHILDREN: RESULTS OF A EUROPEAN RETROSPECTIVE ANALYSIS UNDER THE AUSPICES OF THE EU-RHAB STUDY GROUP. Issue 2 (22nd June 2018) - Benesch, Martin; Neumayer, Petra; Nemes, Karolina; Pietsch, Torsten; Timmermann, Beate; Bison, Brigitte; Warmuth-Metz, Monika; Driever, Pablo Hernáiz; Ebetsberger-Dachs, Georg; Bourdeaut, Franck; Dufour, Christelle; Fouyssac, Fanny; et al.
Abstract: A retrospective European survey was conducted to collect data sets on treatment and outcome of children with intramedullary spinal cord AT/RT. Twelve patients (male, n=4; median age 32 [range, 0.7–97] months) were identified. Lumbar (n=9) and thoracic segments (n=9) were most commonly involved, followed by sacral (n=3) and cervical segments (n=2). In 8 patients more than one spinal cord region was affected. Half of the patients presented with metastatic disease. Primary tumor resection was partial in 6 and gross total in 2 patients. In 4 patients tumors were biopsied only. Central pathology review was performed in 10 patients. Systemic postoperative chemotherapy was administered to all patients. Three patients only received intrathecal therapy and five were irradiated (craniospinal, n=3; local, n=2). Median observation time of the entire cohort was 6 (range, 1–71) months. Three patients, treated according to the EU-RHAB guidelines are alive in complete remission 58, 60, and 71 months after diagnosis. One patient died of intracerebral haemorrhage prior to response evaluation. Five patients progressed early and died within 1–3 months following diagnosis. Three patients died after 7–22 months due to disease progression after having achieved a partial remission (n=1) or disease stabilization (n=2). Event-free and overall survival rates at 1 and (2 years) were 38.9 ± 14.7% (29.2 ± 13.9%) and 41.7 ± 14.2% (25 ± 12.5%), respectively. Spinal cord AT/RT carry a rather grave prognosis. Long-term survival in selected patients is achievable using aggressive multimodality treatment.